2018
DOI: 10.1111/aos.13769
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide association study suggests new evidence for an association of the NADPH Oxidase 4 (NOX4) gene with severe diabetic retinopathy in type 2 diabetes

Abstract: Purpose Diabetic retinopathy is the most common eye complication in patients with diabetes. The purpose of this study is to identify genetic factors contributing to severe diabetic retinopathy. Methods A genome-wide association approach was applied. In the Genetics of Diabetes Audit and Research in Tayside Scotland (GoDARTS) datasets, cases of severe diabetic retinopathy were defined as type 2 diabetic patients who were ever graded as having severe background retinopathy (Level R3) or proliferative retinopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 59 publications
(74 reference statements)
1
28
0
1
Order By: Relevance
“…pol, povišen krvni pritisak, pušenje i gojaznost 5,12,13 . Kada je dijebetesna nefropatija u pitanju, pored navedenih faktora uticaj na razvoj i progresiju bolesti ima i hiperproteinska ishrana 3 .…”
Section: Methodsunclassified
See 3 more Smart Citations
“…pol, povišen krvni pritisak, pušenje i gojaznost 5,12,13 . Kada je dijebetesna nefropatija u pitanju, pored navedenih faktora uticaj na razvoj i progresiju bolesti ima i hiperproteinska ishrana 3 .…”
Section: Methodsunclassified
“…Diabetic retinopathy is the most frequent singular cause of blindness among working people in Great Britain. 5 The estimated number of blind persons, due to diabetic retinopathy and maculopathy is 3.1% in Central and 4.9% in Eastern Europe. 6 Economic consequences, due to vision damage or total loss caused by diabetes are affecting the diseased and their family members, as well as, health systems and society as a whole.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Family studies have further revealed that PDR clusters in families and our previous data suggested a significant genetic component in the pathogenesis of PDR that was as high as 52% ( 10 ). Nevertheless, only a few genetic risk factors have been robustly identified for PDR ( 11 14 ). Therefore, we performed linkage and association analyses in individuals with type 1 diabetes to identify novel susceptibility loci and genes predisposing to PDR and followed up the findings in retinal pigmented epithelial cells.…”
Section: Introductionmentioning
confidence: 99%